Baby’s health record and appointment management system / Wan Nurshahirah Wan Namat - Wan Namat, Wan Nurshahirah (Faculty of Computer and Mathematical Sciences, 2017)
Currently, Department of Mom and Child of Klinik Kesihatan Merlimau, Melaka, is using record books and files to record and manage any appointment with its patients. The management faces some problems to manage the medical record of the children and to organize the appointment manually. Some of the problems are version of the record book are frequently change, parent loss the record book or the book in not good condition, parent forgot the appointment and staff manually arrange the appointment date that sometime mistaken arranged the appointment. Thus, an online of baby’s health record and appointment management system has been developed to help the clinic to organize the medical record and appointment systematically. This system also sends notification a day before the appointment date to the parent through Short Messaging Services (SMS) automatically. Hence, this system allows solving the problem regarding the queue time between the parent’s patients. It also helps the staff to manage the record of children’s health by keeping the history records for future references. Online system developed using PHP, MYSQL, to enable mange the record and appointment management system through online and communication between online system and user smartphone.